A RELATED FIXED POINT THEOREM IN $n$ COMPLETE FUZZY METRIC SPACES - Merghadi, F.; Aliouche, A. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2012)
We prove a related fixed point theorem for $n$ mappings in $n$ fuzzy metric spaces using an implicit relation which generalizes results of Aliouche and Fisher [1] and Rao et al. [13].